Ferric carboxymaltose infusion versus oral iron supplementation for preoperative iron deficiency anaemia in patients with colorectal cancer (FIT): a multicentre, open-label, randomised, controlled trial. Issue 4 (April 2023) - Talboom, Kevin; Borstlap, Wernard A A; Roodbeen, Sapho X; Bruns, Emma R J; Buskens, Christianne J; Hompes, Roel; Tytgat, Kristien M A J; Tuynman, Jurriaan B; Consten, Esther C J; Heuff, Gijsbert; Kuiper, Teaco; van Geloven, Anna A W; et al.
Summary: Background: A third of patients with colorectal cancer who are eligible for surgery in high-income countries have concomitant anaemia associated with adverse outcomes. We aimed to compare the efficacy of preoperative intravenous and oral iron supplementation in patients with colorectal cancer and iron deficiency anaemia. Methods: In the FIT multicentre, open-label, randomised, controlled trial, adult patients (aged 18 years or older) with M0 stage colorectal cancer scheduled for elective curative resection and iron deficiency anaemia (defined as haemoglobin level of less than 7·5 mmol/L (12 g/dL) for women and less than 8 mmol/L (13 g/dL) for men, and a transferrin saturation of less than 20%) were randomly assigned to either 1–2 g of ferric carboxymaltose intravenously or three tablets of 200 mg of oral ferrous fumarate daily. The primary endpoint was the proportion of patients with normalised haemoglobin levels before surgery (≥12 g/dL for women and ≥13 g/dL for men). An intention-to-treat analysis was done for the primary analysis. Safety was analysed in all patients who received treatment. The trial was registered at ClincalTrials.gov, NCT02243735, and has completed recruitment. Findings: Between Oct 31, 2014, and Feb 23, 2021, 202 patients were included and assigned to intravenous (n=96) or oral (n=106) iron treatment. Treatment began a median of 14 days (IQR 11–22) before surgery for intravenous iron and 19 days (IQR 13–27) for oral iron. Normalisation of haemoglobin at day of admission was reached in 14 (17%) of 84 patients treated intravenously and 15 (16%) of 97 patients treated orally (relative risk [RR] 1·08 [95% CI 0·55–2·10]; p=0·83), but the proportion of patients with normalised haemoglobin significantly increased for the intravenous treatment group at later timepoints (49 [60%] of 82 vs 18 [21%] of 88 at 30 days; RR 2·92 [95% CI 1·87–4·58]; p<0·0001). The most prevalent treatment-related adverse event was discoloured faeces (grade 1) after oral iron treatment (14 [13%] of 105), and no treatment-related serious adverse events or deaths were observed in either group. No differences in other safety outcomes were seen, and the most common serious adverse events were anastomotic leakage (11 [5%] of 202), aspiration pneumonia (5 [2%] of 202), and intra-abdominal abscess (5 [2%] 202). Interpretation: Normalisation of haemoglobin before surgery was infrequent with both treatment regimens, but significantly improved at all other timepoints following intravenous iron treatment. Restoration of iron stores was feasible only with intravenous iron. In selected patients, surgery might be delayed to augment the effect of intravenous iron on haemoglobin normalisation. Funding: Vifor Pharma.